The adipose tissue keeps the score: priming of the adrenal-adipose tissue axis by early life stress predisposes women to obesity and cardiometabolic risk - Turner, Meghan Blair; Dalmasso, Carolina; Loria, Analia S. (Frontiers in Endocrinology, 2024)
Adverse Childhood Experiences (ACEs) refer to early life stress events, including abuse, neglect, and other psychosocial childhood traumas that can have long-lasting effects on a wide range of physiological functions. ACEs provoke sex-specific effects, whereas women have been shown to display a strong positive correlation with obesity and cardiometabolic disease. Notably, rodent models of chronic behavioral stress during postnatal life recapitulate several effects of ACEs in a sex-specific fashion. In this review, we will discuss the potential mechanisms uncovered by models of early life stress that may explain the greater susceptibility of females to obesity and metabolic risk compared with their male counterparts. We highlight the early life stress-induced neuroendocrine shaping of the adrenal-adipose tissue axis as a primary event conferring sexdependent heightened sensitivity to obesity.